Telaah Konsensus Privacy Policy Sebagai Kontrak Digital pada E-Commerce Guna Memberikan Perlindungan Data Pribadi - Salsabila, Elora; Sulistiyono, Adi (Primagraha Law Review, 2024)
This research is motivated by the phenomenon of personal data misuse occurring in various e-commerce platform. E-commerce platforms inherently have the authority and full responsibility over the collection, processing, and utilization of personal data through profiling activities. The policy regarding these activities is regulated an included in the digital agreement document called the “Policy Privacy”. This study aims to examine whether the “Privacy Policy” has obtained sufficient validity of agreement form e-commerce service users, considering the consensus given appears to be coercive. Moreover, many clauses in these "Privacy Policies" often transfer the legal protection of personal data responsibilities to the users, thus this can be classified as an exemption clauses. This research is a normative juridical study that utilizes legal approach, case approaches, and conceptual approaches to examine the involvement of various laws and the application of the pacta sunt servanda principal in creating fair legal protection for consumers' personal data. The results obtained indicate that agreement on the “Privacy Policy” can be considered to have the same validity as other conventional agreements. However, there is a need for further development of supervision and provisions regarding the use of the “Privacy Policy”.